FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PEMANFAATAN LIMBAH PETERNAKAN SAPI POTONG DI KECAMATAN SUWAWA SELATAN - Kusmawan, Muzdalifa; R, St. Aisyah; Sirajuddin, Zulham (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Cattle farming needs to prioritize sustainable waste management. The productivity of beef cattle farming is not yet fully maximized because it still uses conventional farming practices. The objectives of the study: (1) to identify the characteristics of beef cattle farmers in South Suwawa District and (2) to examine the factors that influence the implementation of farmers in waste utilization. The study used a sample of 60 farmers through accidental sampling. This study used the SPSS 23 Program with multiple regression analysis. The results of the study showed (1) age, education, gender, occupation, and experience of cattle farmers have an impact on the management of waste utilization efforts and (2) the significance test (t-test) and (f-test) showed that the variables representing the knowledge aspect (X1) and attitude aspect (X2) did not have a statistically significant or real effect. Although environmental factors (X3) have the same impact. The importance of farmer behavior in increasing understanding and changing attitudes to minimize environmental pollution and contribute to achieving zero waste goals.